2018
DOI: 10.1038/s41467-018-07150-9
|View full text |Cite|
|
Sign up to set email alerts
|

Integrating chemical and mechanical signals through dynamic coupling between cellular protrusions and pulsed ERK activation

Abstract: The Ras-ERK signaling pathway regulates diverse cellular processes in response to environmental stimuli and contains important therapeutic targets for cancer. Recent single cell studies revealed stochastic pulses of ERK activation, the frequency of which determines functional outcomes such as cell proliferation. Here we show that ERK pulses are initiated by localized protrusive activities. Chemically and optogenetically induced protrusions trigger ERK activation through various entry points into the feedback l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 65 publications
(76 reference statements)
8
59
0
Order By: Relevance
“…Perturbations equivalent to oncogenic mutations alter the wave properties, causing cells to display wider or longer, narrower protrusions (4,8). Human cancer cell lines also display altered morphology and migratory behavior which can be traced to network excitability (9,10).…”
Section: Pten -/-mentioning
confidence: 99%
“…Perturbations equivalent to oncogenic mutations alter the wave properties, causing cells to display wider or longer, narrower protrusions (4,8). Human cancer cell lines also display altered morphology and migratory behavior which can be traced to network excitability (9,10).…”
Section: Pten -/-mentioning
confidence: 99%
“…Studies in Dictyostelium have shown that in the absence of signal transduction, these cytoskeletal events generate short, narrow protrusions, whereas coupling of STEN and CEN produces waves at the edge of cells followed by forward expansion of the membrane in the form of pseudopodia or broad lamellipodia-like protrusions , Miao et al, 2019, Tang et al, 2014, Vicker, 2002. Such correlations between signal transduction and actin waves, and leading edge protrusions are also found in mammalian cells such as neutrophils (Weiner et al, 2007), fibroblasts (Jalal et al, 2019, Zhang et al, 2018, keratocytes (Barnhart et al, 2011) and cancer cells (Yang et al, 2018).…”
Section: Role Of Excitability In Dictyostelium and Mammalian Cellsmentioning
confidence: 92%
“…2F), suggesting a loss of coordinated retraction and repolarisation of lamellae after collision. Interestingly, ERK proteins were recently shown to regulate various cytoskeletal and migratory behaviours (Yang et al, 2018; Mendoza et al, 2011; Aoki et al, 2017) and we hypothesise that the ERK family is a good candidate to modulate distinct CIL dynamics.…”
Section: Resultsmentioning
confidence: 93%